Corelation Between Driving Position and Other Factor to Musculoskeletal Complaints with Reba in Online Taxibike Drivers in West Jakarta 2021 - Winata, Susanty Dewi; Mariyamah, Titis; Satyadi, Erdi Techrisna; Hersamsi, Giovani Sabrina; Purnamawati, Purnamawati (Universitas Kristen Krida Wacana, 2023)
Poor posture is the main cause of Musculoskeletal Disorders, MSDs in motorcyclists can affect daily activities, reduce work efficiency and productivity, increase the risk of work accidents and long-term illness. This study aims to determine whether there is a relationship between driving position and musculoskeletal disorders with the Rapid Entire Body Assessment hoping that the complaints can be minimized or prevented. Research data collection took place in December 2021. Research participants were online taxibike drivers in West Jakarta who were still actively working in 2021. Demographic data and riding position were obtained through the Nordic Body Map questionnaire and online questionnaire via Google Form. For the riding position, respondents were asked to ride the motorbike they used for work and were photographed by the researcher, and calculated using the REBA calculator software. The statistical test showed a value of P: 0.682 (p> 0.05) which indicated that there was no significant relationship between riding position and musculoskeletal complaints among online motorcycle drivers in West Jakarta in 2021. Even though there was no relationship between riding position and musculoskeletal complaints, to reduce the increased risk of MSDs, riders can make the best use of their rest time outside of work hours or before work by doing small sports or stretching to stretch tense muscles and reduce the accumulation of lactic acid.